Shadows of Forgotten Ancestors: In search of national representation in the image of folklore. Issue 1 (1st June 2021) - Ovtchinnikova, Alexandra
In this case study analysis of the film Shadows of Forgotten Ancestors (1965) directed by Sergei Parajanov (1924‐90) I will explore the ways in which traditional dress in this film, as part of a wider imagery of folklore, has been defamiliarized from the ideological canon of social realism. More specifically, I will look at the ways Parajanov's film, filled with music, dance, colour and ethnographic texture, significantly departed from the traditional representation of non-Russians on the Soviet screen under the Friendship of Peoples policy. Based on a folkloric legend, adapted and published in 1911 by Mykhailo Kotsiubynskyi (1864‐1913), Shadows celebrates the ethnographic texture of the Hutsul region by departing significantly from causality and narrative logic and bringing together primitive and modern elements instead. Praised for its authenticity, the film became a turning point in the search for a new site of national expression for Ukrainian filmmakers and more specifically, the role of folklore in its visual presentation. The work of the costume designer Lidiya Bajkova (1905‐80) is emblematic in the way it renders authenticity beyond historical, ethnic and material accuracy by seamlessly integrating the costumes into the visual texture of the cinematic image. Her approach demonstrates how motifs and patterns that have previously been delegated to domesticated and melodramatic narratives could conversely become a fundamental substance of the cinematic experience.